2019
DOI: 10.1002/adsc.201801530
|View full text |Cite
|
Sign up to set email alerts
|

Aldolase‐Catalyzed Asymmetric Synthesis of N‐Heterocycles by Addition of Simple Aliphatic Nucleophiles to Aminoaldehydes

Abstract: Nitrogen heterocycles are structural motifs found in many bioactive natural products and of utmost importance in pharmaceutical drug development. In this work, a stereoselective synthesis of functionalized N‐heterocycles was accomplished in two steps, comprising the biocatalytic aldol addition of ethanal and simple aliphatic ketones such as propanone, butanone, 3‐pentanone, cyclobutanone, and cyclopentanone to N‐Cbz‐protected aminoaldehydes using engineered variants of d‐fructose‐6‐phosphate aldolase from Esch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…The acceptor displays an even wider substrate range, including aromatic aldehydes. [130][131][132][133][134][135] 2.1.2.4. Glycine dependent aldolases.…”
Section: Pyruvate Dependent Aldolasesmentioning
confidence: 99%
“…The acceptor displays an even wider substrate range, including aromatic aldehydes. [130][131][132][133][134][135] 2.1.2.4. Glycine dependent aldolases.…”
Section: Pyruvate Dependent Aldolasesmentioning
confidence: 99%
“…Pyrido and pyrrolo [1,2-c] [1,3] oxazin-1-ones (cis-or trans-), as well as 3-hydroxy-2substituted piperidine scaffold, [2] serve as building blocks and core skeletons for numerous alkaloids, pharmaceutical candidates and drugs through valuable contributions to the synthetic and medicinal chemistry. As a prime instance, antimalarial alkaloids (+)-Febrifugine (1) and (+)-IsoFebrifugine (2) (Figure 1), isolated from Chinese medicinal plants Dichroa febrifuga Lour. (Chang Shan [3] ) and related hydrangea plants, [4] contain the typical 3-hydroxy-2-substituted piperidine scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…Clapes et al have demonstrated the synthesis of many iminosugars using the chemoenzymatic combination of D-fructose-6phosphate aldolase (FSA) and palladium mediated hydrogenation. [6][7][8] Using these methods, the synthesis of several pharmaceutically relevant iminosugars such as 1-deoxynojirimycin (1-DNJ) have been achieved. Several other aldolases have also been applied to the synthesis of iminosugars, with the biocatalytic preparation of Dfagomine from glycerol and N-Cbz-3-aminopropanal via a multi-step cascade in a flow reactor.…”
Section: Mainmentioning
confidence: 99%